Исследования показателей качества сортовых вин Санджовезе и Сира - Цыганкова, Елена Викторовна; Билько, Марина Владимировна (My University, 2015)
В данной статье представлены результаты исследований розовых и красных столовых сухих вин из сортов винограда Санджовеже и Сира, произведенных в Аргентине, Греции, Израиле, Испании, Италии, Чили. Проведен сравнительный анализ органолептической оценки, физико-химических характеристик, биологической ценности по фенольному комплексу, окислительно-восстановительного состояния с винами, произведенными в Украине из данных сортов винограда. This article presents the results of studies of rose and red table wines from dry grapes Sandzhovezhe and Syrah produced in Argentina, Greece, Israel, Spain, Italy, Chile. A comparative analysis of organoleptic evaluation, physical and chemical characteristics, biological value at phenolic complex, the redox state of the wines produced in Ukraine from these grapes. It is shown that wine materials produced from grapes cultivated in the conditions of Ukraine are not inferior to foreign models according the organoleptic characteristics of wines from these grapes, and they also have a biological value and oxidation resistance. It is proved that for the production of red wines of high biological value from the grapes Sandzhovezhe and Syrah the grapes must be processed with the intensification of must and pulp contact.
Keywords: розе; Сира; красные вина; органолептика; фенольные вещества; биологическая ценность; Sangiovese; Syrah; red wines; rose; organoleptic evaluation; phenolic substances; biological value; кафедра біотехнології продуктів бродіння і виноробства